BANKS AS SECURITY ACTORS countering terrorist financing at the human-technology interface. - Bosma, Esmé (ROUTLEDGE, 2025)
This book analyses how banks implement counter-terrorist financing measures and experiment with technologies to assess risks and make security decisions.Banks have become private security actors. As "gatekeepers" of the financial system, they are legally obliged to conduct customer research and monitor bank accounts for unusual or suspicious transactions. Given the sheer volume of financial transactions that banks process daily, detection of financial crime heavily relies on digital security technologies that help analysts categorise and identify risky customers and financial transactions. Drawing from theories at the intersection of International Relations and Science and Technology Studies, the book advances the concept of 'de-scription' to offer a framework for analysing experimentation with security and digital technologies in practice. The research is based on fieldwork conducted in the financial crime sector in the Netherlands and the United Kingdom. It explores how political and ethical choices materialise at the human-technology interface and analyses the production of customer risk profiles, the design and use of transaction monitoring systems, and the emergence of public-private partnerships to counter terrorist financing.This book will be of interest to students and researchers in International Relations, Science and Technology Studies, and Critical Security Studies.
Keywords: Terrorism -- Finance.; Banks and banking.; elektronické knihy; electronic books